2013
DOI: 10.1021/la4011086
|View full text |Cite
|
Sign up to set email alerts
|

Superamphiphobic Surface by Nanotransfer Molding and Isotropic Etching

Abstract: We present a novel method of fabricating superhydrophobic and superoleophobic surfaces with nanoscale reentrant curvature by nanotransfer molding and controlled wet etching of the facile undercut. This method produces completely ordered re-entrant nanostructures and prevents capillary-induced bundling effects. The mushroom-like, re-entrant, overhanging structure demonstrates superhydrophobic and superoleophobic characteristics, as tested by water droplet bouncing and contact angle measurements, and has high tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(36 citation statements)
references
References 42 publications
(57 reference statements)
0
36
0
Order By: Relevance
“…In the literature, it was shown that surface topographies with reentrant curvatures or multivalued roughness such as mushroom-like structures or overhangs can produce superoleophobic properties. [5][6][7][8][9][10][11] Here, we show that different surface morphologies can lead to superoleophobic properties but the presence of thin fi bers allow to reach such properties even if the roughness is low ( R a ≈ 0.2 µm) while higher roughness are necessary with spherical particles ( R a ≈ 2 µm).…”
Section: Discussionmentioning
confidence: 95%
“…In the literature, it was shown that surface topographies with reentrant curvatures or multivalued roughness such as mushroom-like structures or overhangs can produce superoleophobic properties. [5][6][7][8][9][10][11] Here, we show that different surface morphologies can lead to superoleophobic properties but the presence of thin fi bers allow to reach such properties even if the roughness is low ( R a ≈ 0.2 µm) while higher roughness are necessary with spherical particles ( R a ≈ 2 µm).…”
Section: Discussionmentioning
confidence: 95%
“…Superhydrophobic surfaces are typically only repellent to water or liquids having high surface tension (e.g., Y lv for water = 72.1 mN/m). For example, the superhydrophobic lotus leaf surface can be easily wetted by organic liquids and oils with low surface tension …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the overhang part of the grooved sidewall develops a predetermined breaking point that makes the re-entrant structures more fragile10. As such, the arrays of extruded structures46711121314 are easily disrupted under external abrasion15 and can even collapse from the capillary forces for nanoscale structures16. This greatly restricts practical applications of liquid-repellent surfaces.…”
mentioning
confidence: 99%